An Experimental Study on the Interaction Law of the Pore Gas Pressure and Stress in Gassy Coals - Zuxiang Hu; Jian Sun; Mingyun Tang (Tehnički Vjesnik, 2018)
Understanding the principle underlying the coupling between coal seam stress and gas pressure will help prevent the occurrence of dynamic coal and gas disasters. However, previous studies have mainly focused on the macroscopic qualitative analyses of the coupling between coal seam stress and gas pressure. In fact, laboratory quantitative tests, which investigate gas pressure in sealed sample tanks, fail to represent the essential relationship between stress and gas pressure in real time. In this study, a model of the stress–porosity–gas pressure relationship was established based on the pore characteristics of gassy coals and gas adsorption theory to quantify the coupling between coal seam stress and gas pressure. In addition, a method for determining the law governing stress and gas pressure coupling was proposed based on stress–strain curves obtained through triaxial loading tests. Results show that the porosity and gas pressure of gassy coals first decrease and then increase as loading stress increases. Under various confining pressures and initial gas pressures, porosity declines at a lower rate with the increase in the initial gas pressure. Specifically, gas pressure increases with stress before the value of stress reaches that of the compressive strength of the coal. This behaviour demonstrates that gas pressure and stress are positively correlated. High initial gas pressures are associated with small increments (i.e., from 136% to 30%) in pore gas pressure under stress. When stress exceeds the compressive strength of the coal, gas pressure begins to decrease with stress. Thus, stress and gas pressure are negatively correlated. Finally, the validity of the research method was verified through afield experiment. The proposed method provides new concepts for the study of the mechanism, prevention, and control technology of dynamic coal and gas disasters.